2009
DOI: 10.1590/s0103-97332009000500017
|View full text |Cite
|
Sign up to set email alerts
|

Inter hydrogen bonded complexes of hexadecylaniline and alkoxy benzoic acids: a study of crystallization kinetics

Abstract: A systematic crystallization kinetic study of two smectogens of homologous series of the inter molecular hydrogen bonded between undecyl, dodecyl benzoic acids and hexadecylaniline complexes viz., 16A+11BA and 16A+12BA respectively has been carried out by thermal microscopy, differential scanning calorimetry (DSC) and dielectric studies. FTIR studies indicate the formation of hydrogen bond in these complexes. The crystallization kinetics was studied by two techniques viz., the traditional thermal analysis (DSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The phase sequence of the levo tartaric acid and undecyloxy benzoic acid (LTA+11BA) hydrogen bonded complex in the cooling run can be shown as: The phase diagrams of pure p-n-alkoxy benzoic acids and the present homologous series (nBA+LTA) are constructed and reported [30] through optical polarizing microscopic studies by the phase transition temperatures observed in the cooling run of the mesogens of the present homologous series. The phase diagram of pure p-n-alkoxy benzoic acids is reported [24] to exhibit three phases namely, Nematic, smectic C* and smectic G*.…”
Section: Palte4mentioning
confidence: 99%
See 1 more Smart Citation
“…The phase sequence of the levo tartaric acid and undecyloxy benzoic acid (LTA+11BA) hydrogen bonded complex in the cooling run can be shown as: The phase diagrams of pure p-n-alkoxy benzoic acids and the present homologous series (nBA+LTA) are constructed and reported [30] through optical polarizing microscopic studies by the phase transition temperatures observed in the cooling run of the mesogens of the present homologous series. The phase diagram of pure p-n-alkoxy benzoic acids is reported [24] to exhibit three phases namely, Nematic, smectic C* and smectic G*.…”
Section: Palte4mentioning
confidence: 99%
“…With our previous experience [23][24][25][26][27][28][29][30], in designing, synthesizing and characterizing various types of liquid crystals, a successful attempt has been made in characterizing a novel series of inter hydrogen bonded liquid crystal exhibiting optical shutter activity in cholesteric phase of LTA+11BA hydrogen bonded complex.…”
Section: Introductionmentioning
confidence: 99%
“…Low doping concentrations (<3% by weight) are usually preferred to get a more stable and for an even distribution in the LC, which will lower the interaction forces between particles [3,4]. --alkyloxybenzoic acids are extensively studied earlier and gained interesting results [5][6][7][8]. Various experimental techniques are being done on these alkyloxybenzoic acids on individual members and on mixed compounds [6,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Many liquid crystal systems like molecular liquid crystals [22][23][24][25][26], polymer liquid crystals [27][28][29][30][31], ferroelectric liquid crystals [32,33], and even room temperature liquid crystals have been prepared [8]. Single bond [34][35][36], double bond [37][38][39][40], and even multiple bond [41,42] hydrogen-bonded liquid crystals are synthesized and reported.…”
Section: Introductionmentioning
confidence: 99%